Promoting Innovative Performance in Multidisciplinary Teams: The Roles of Paradoxical Leadership and Team Perspective Taking - Li, Quan; She, Zhuolin; Yang, Baiyin (Frontiers in Psychology, 2018)
Although many researches recognize the role of team expertise diversity in providing different ideas, it remains unclear how and under which conditions these various ideas are elaborated and integrated to fuel team innovation. To address this question, we develop a model theorizing that paradoxical leadership helps diverse teams overcome the differentiating-integrating paradox to promote innovation. Moreover, we further theorize that paradoxical leadership will cultivate perspective taking among team members. Analyses of the multi-time and multi-source data from 98 teams suggest that teams with expertise diversity exhibit better innovative performance when paradoxical leadership is prevalent. Furthermore, team perspective taking mediates the positive moderating effects of paradoxical leadership on the relationship between expertise diversity and innovative performance. Through these analyses, this study not only addresses the innovation paradox of expertise diverse teams from the perspective of leader influence, but also enriches the understanding of the effects of paradoxical leadership.